Determinants of eGFR at start of renal replacement therapy in paediatric patients - Stralen, Karlijn J. van; Tizard, E. Jane; Jager, Kitty J.; Schaefer, Franz; Vondrak, Karel; Groothoff, Jaap W.; Podracká, Ludmila; Holmberg, Christer; Jankauskiené, Augustina; Lewis, M. A.; van Damme-Lombaerts, Rita; Mota, Conceição; et al. (Nephrology, dialysis, transplantation, 2010)
Few studies have investigated the determinants of glomerular filtration rate (GFR) in paediatric patients starting on dialysis or with a transplant.